1990
DOI: 10.4039/ent1221119-11
|View full text |Cite
|
Sign up to set email alerts
|

FACTORS AFFECTING CATCH IN PHEROMONE TRAPS FOR MONITORING THE WESTERN SPRUCE BUDWORM, CHORISTONEURA OCCIDENTALIS FREEMAN

Abstract: The effects of trap design, lure concentration, lure age, and trap maintenance on the catch of western spruce budworm moths, Choristoneura occidentalis Freeman, in pheromone traps were tested in light to moderate infestations near Ashcroft, B.C. High cumulative moth catches reduced the trapping efficiency of both the sticky traps and the non-sticky Uni-traps relative to traps from which the moths were removed every 2 days. Correlations between the total season’s catch and larval density per plot in the same an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Trap design, placement and density can also affect the number of moths captured (Cuevas et al, 1983a;Einhorn et al, 1983;Ramaswamy and Carde, 1982;Subchev et al, 1994;Tiberi and Niccoli, 1984;Lopez, 1998;Cork et al, 2003). Yet another factor may be trap saturation, with many studies showing a decrease in trap efficiency with increasing number of catches (Ramaswamy and Carde, 1982;Allen et al, 1986;Elkinton, 1987;Sweeney et al, 1990;Gray et al, 1991;Thorpe et al, 1993;Morewood et al, 2000). Some authors describe a decrease in pheromone-trap efficiency with increasing local insect population density, interpreting it as a result of competition between pheromone dispensers and numerous wild females for male attraction (Cornic et al, 1986;Taylor et al, 1991).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Trap design, placement and density can also affect the number of moths captured (Cuevas et al, 1983a;Einhorn et al, 1983;Ramaswamy and Carde, 1982;Subchev et al, 1994;Tiberi and Niccoli, 1984;Lopez, 1998;Cork et al, 2003). Yet another factor may be trap saturation, with many studies showing a decrease in trap efficiency with increasing number of catches (Ramaswamy and Carde, 1982;Allen et al, 1986;Elkinton, 1987;Sweeney et al, 1990;Gray et al, 1991;Thorpe et al, 1993;Morewood et al, 2000). Some authors describe a decrease in pheromone-trap efficiency with increasing local insect population density, interpreting it as a result of competition between pheromone dispensers and numerous wild females for male attraction (Cornic et al, 1986;Taylor et al, 1991).…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, Baronio et al (1994) observed a significant relationship between densities of winter nests and sum captures of T. pityocampa males in the same pine stands. In addition, pheromone-based monitoring has been used successfully for many other forest moths, such as the eastern spruce budworm (Ramaswamy et al, 1983;Allen et al, 1986;Sanders, 1988), the western spruce budworm (Sweeney et al, 1990), the gypsy moth (Ravlin, 1991), the nun moth (Morewood et al, 2000) and the western hemlock looper (Evenden et al, 1995). Monitoring systems based on pheromone trapping have even been developed to predict defoliation (Shepherd et al, 1985;Thorpe et al, 1993;Evenden et al, 1995;Sanders, 1996).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Non-saturating traps can retain large numbers of insects, which is particularly useful when traps remain in the field for the duration of the flight period. Even non-saturating Unitraps were less efficient in capturing western spruce budworm moths, Choristoneura occidentalis (Walsingham) (Lepidoptera: Tortricidae), when traps were not regularly maintained throughout the flight season (Sweeney et al 1990). Captured moths will decay if traps are deployed for long periods, and this can affect moth orientation to the trap (Sanders 1986b) and make the sample difficult to count.…”
Section: Monitoring Forest Defoliatorsmentioning
confidence: 99%
“…If this relationship is robust, pheromone-based monitoring can replace more costly sampling techniques such as foliage samples, or samples of immature stages (Sanders 1988). These types of relationships have been established for forest defoliators in Canada by sampling populations over long periods of time (Sanders 1988) or targeting populations of differing densities over a condensed period (Shepherd et al 1985;Sweeney et al 1990;Evenden et al 1995a).…”
Section: Monitoring Forest Defoliatorsmentioning
confidence: 99%